ANALISIS PERHITUNGAN, PEMOTONGAN DAN PEMAHAMAN TENTANG PPH PASAL 21 KARYAWAN PT KUALA PELABUHAN INDONESIA DEPT LOGISTIC OPERATION SUPPORT - Yahya Nusa (JURNAL ULET (Utility, Earning and Tax), 2019)
This study aims to determine the Calculation and Withholding of Income Tax Article 21 Employees of PT Kuala Pelabuhan Indonesia DePT Logistic Operation Support whether it is in accordance with applicable tax laws and regulations and to understand understanding of Employees PT Kuala Pelabuhan Indonesia DePT Logistic Operation Support on Calculation and Withholding Income Tax Article 21 each month. From this research, the data obtained is to compare the calculation of Income Tax Article 21 in accordance with the laws and the applicable tax laws with the salary slip received by the employees every month. As well as conducting interviews directly and filling out questionnaires by employees of PT Kuala Pelabuhan Indonesia DePT Logistic Operation Support by taking 50 employees as a sample to know whether the recipient employees whose monthly deductions pph Article 21 understand the mechanism of calculation and cutting pph Article 21 by the employer. The result of research shows that PT Kuala Pelabuhan Indonesia DePT Logistic Operation Support has conducted the calculation and withholding mechanism of Article 21 of the employee in compliance with applicable tax laws and regulations, but the mechanism of calculation and withholding of Article 21 tax is not understood by most employees PT Kuala Pelabuhan Indonesia DePT Logistic Operation Support.